Field-Induced Single Molecule Magnets of Phosphine- and Arsine-Oxides - Fondo, Matilde; Corredoira-Vázquez, Julio; García-Deibe, Ana M.; Sanmartín-Matalobos, Jesús; Herrera, Juan Manuel; Colacio, Enrique (Frontiers in Chemistry, 2018)
The coordination chemistry of dysprosium and terbium towards phosphine and arsine oxides was further explored. Thus, the new nitrate [M(NO3)3(Ph3PO)3] (M = Tb, 1; Dy, 2), [Dy(NO3)3(EtOH)(Ph3XO)2] (X = P, 3; As, 4), chloride [DyCl2(Ph3AsO)4]Cl (5), triflate [Dy(OTf)2(MePh2PO)4]OTf (6; OTf = triflate) and hexafluoroacetylacetonate [M(hfa)3(Ph3PO)2] (hfa = hexafluoroacetylacetonate; M = Tb, 7; Dy, 8) complexes were isolated and fully characterized. The crystal structures of 1·CH3CN, 2·CH3CN, 4, 5·2.75EtOH·1.25H2O, 6, 7 and 8 show MO9 cores in 1, 2 and 4, with highly distorted geometry, between spherical capped square antiprism and muffin like, hexacoordinated environments for the dysprosium ions in 5 and 6, with octahedral geometry, and octa-coordination for the lanthanoid metals in 7 and 8, with geometry closer to square antiprism. Comparison of the magnetic behavior of all the complexes allows analyzing which metal ion (Tb or Dy), phosphine or arsine oxide, or anionic ligand favor more the slow relaxation of the magnetization. Alternating current magnetic measurements show that only 2, 4 and 8 present slow relaxation of the magnetization in the presence of an external magnetic field, 8 being the complex with the highest Ueff (44.85 K) of those described herein.